(3GdMeGSI GdHUQjIs - (3Ydj Hf CHj GdaQL Hf GdMSf, UOQ GdOjf, CHh GdMSf GdHUQj,J (B659 (3g` s
(3ChdgG (B:s
(3jHOC CKfGA HGH GdZRd hGhdGdehLhO efgG (B: (3aCjGf GdMdi hGdWjH YeG SJQJg ef CeQfG GdeSJhQ s
(3BNQgG (B:s
(3adG CeSc GdeGVi Ydjc HQGLY hdG ZOc GdBJi Hg CfJ hGKb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B98 - (3U(B178s
(3bWYI efgGs
(3jJdhG GdcJGH ebWhYGJ bjOJ HYO JeGegs
(3Ke JbQjXGJ ddMeGSI GdHUQjI dcKjQ ef GdCOHGA hGdYdeGAs
(3cJHJ CSeGA GdTYQGA HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdCOHs